If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(7)=0
We simplify the equation to the form, which is simple to understand
-9(7)=0
Reorder the terms in parentheses
+(-63)=0
Remove unnecessary parentheses
-63=0
We move all terms containing to the left and all other terms to the right.
0=0+63
We simplify left and right side of the equation.
0=+63
0=63
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 32x^2/990^2 | | 164=6x-4(-4x+3) | | x^3-5x^2-12x=0 | | X-1=4x+3 | | 4x-4-3x+52=180 | | 6u+4u-(-6u)-15u-6=9 | | 1/8y=-17 | | 2(3-4x)=3(2x+5) | | 2.4x+11.3=3.7-0.6 | | 26(x-2)+3(4-x)=25 | | 0.75x+13.25=1.25x+12 | | 7x+2x+4x-10x-x=20 | | (2.4x)+11.3=3.7-(0.6x) | | 70-2x=210-42x | | -2x-2(3x+5)=-106 | | 2x^2+25x-3=0 | | X-4(2X-3)=26 | | 2x^2=82 | | 2=2.27-s-4 | | .09n=600-0.12n+198 | | X-4(2X-30)=26 | | -2x-4(-6-10)=-136 | | 5u+11=111 | | 6n+24= | | 67-2x=83-3x | | 0.22m=0.1m+15.60 | | (5x^3y/20xy^5)^4 | | 13X=-X^2-12 | | (12x+7)+(3x^2-12x-5)= | | 3x^2-32x+75=0 | | 26x-2=8x+3+85 | | 502.08+1.6= |